From Selective Exposure to Selective Information Processing: A Motivated Reasoning Approach - Camaj, Lindita (2019)
Literature suggests that while without doubt people engage in selective exposure to information, this does not entail that they also engage in selective avoidance of opinion-challenging information. However, cross-cutting exposure does not always lead to dispassionate deliberation. In this commentary I explore psychological conditions as they apply to attitude-based selection and make an argument that selectivity does not stop at exposure but continues as audiences engage with information they encounter and incorporate in their decision-making. I propose the theory of motivated reasoning as a rich theoretical underpinning that helps us understand selective exposure and selective information processing.